DNA Methylation-Mediated Modulation of Endocytosis as Potential Mechanism for Synaptic Function Regulation in Murine Inhibitory Cortical Interneurons. (7th March 2020) - Pensold, Daniel; Reichard, Julia; Van Loo, Karen M J; Ciganok, Natalja; Hahn, Anne; Bayer, Cathrin; Liebmann, Lutz; Groß, Jonas; Tittelmeier, Jessica; Lingner, Thomas; Salinas-Riester, Gabriela; Symmank, Judit; et al.
Abstract: The balance of excitation and inhibition is essential for cortical information processing, relying on the tight orchestration of the underlying subcellular processes. Dynamic transcriptional control by DNA methylation, catalyzed by DNA methyltransferases (DNMTs), and DNA demethylation, achieved by ten–eleven translocation (TET)-dependent mechanisms, is proposed to regulate synaptic function in the adult brain with implications for learning and memory. However, focus so far is laid on excitatory neurons. Given the crucial role of inhibitory cortical interneurons in cortical information processing and in disease, deciphering the cellular and molecular mechanisms of GABAergic transmission is fundamental. The emerging relevance of DNMT and TET-mediated functions for synaptic regulation irrevocably raises the question for the targeted subcellular processes and mechanisms. In this study, we analyzed the role dynamic DNA methylation has in regulating cortical interneuron function. We found that DNMT1 and TET1/TET3 contrarily modulate clathrin-mediated endocytosis. Moreover, we provide evidence that DNMT1 influences synaptic vesicle replenishment and GABAergic transmission, presumably through the DNA methylation-dependent transcriptional control over endocytosis-related genes. The relevance of our findings is supported by human brain sample analysis, pointing to a potential implication of DNA methylation-dependent endocytosis regulation in the pathophysiology of temporal lobe epilepsy, a disease characterized by disturbed synaptic transmission.